2008
DOI: 10.1097/ijg.0b013e3181567890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Modified Protocol for Selective Laser Trabeculoplasty

Abstract: Overlapping application of SLT results in a poorer IOP response compared with ALT and nonoverlapping SLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
3
19
0
3
Order By: Relevance
“…Consistent with earlier reports, [16][17][18][19] we found a positive correlation between pretreatment IOP and IOP reduction rate for 360-degree SLT. The lower the pretreatment IOP was, the lower the IOP reduction rate became.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with earlier reports, [16][17][18][19] we found a positive correlation between pretreatment IOP and IOP reduction rate for 360-degree SLT. The lower the pretreatment IOP was, the lower the IOP reduction rate became.…”
Section: Discussionsupporting
confidence: 94%
“…George et al 19 compared the outcomes of 100 overlapping laser spots over 180-degree SLT with 100 nonoverlapping spots over 360-degree SLT and reported the former showed poorer IOP response than the latter. This suggests that there might be an optimal area for SLT application and an optimal number of laser spots for the best IOP reduction.…”
Section: Discussionmentioning
confidence: 98%
“…Also this study is consistent with Mao et al8 who reported a positive association between laser efficacy and IOP before SLT treatment. Our results are also in line with the results presented by George et al9 who found that baseline IOP was the only preoperative predictive factor for response to ALT and non overlapping SLT.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, in a retrospective review of 318 eyes of 284 OAG patients, using 100 overlapping SLT spots over 180 degrees had a poorer IOP response than those treated with nonoverlapping SLT spots over 360 degrees. 17 Thus, it seems that a greater number of spots may not be directly related to SLT success but the extent of trabecular meshwork treatment also seems to play a role. Rinke et al 18 reported that a higher effectiveness was achieved with 360 degrees SLT treatment compared with 180 degrees treatment in 36 eyes with OAG.…”
Section: Discussionmentioning
confidence: 97%